อุบัติการณ์และคุณสมบัติของเชื้อเอสเชอริเชียโคไลดื้อยาหลายขนานในเนื้อสัตว์ปีก - Tansawai, Uttapoln; Ritvirool, Pannik (Naresuan University Journal: Science and Technology (NUJST); Vol 22 No 2 (2014): May-August 2014, 2014)
การศึกษาบทบาทของเนื้อสัตว์ปีกในการเป็นแหล่งของแบคทีเรียดื้อยา โดยเก็บตัวอย่างเนื้อสัตว์ปีก (เนื้อไก่และเนื้อเป็ด) ที่ขายในซูเปอร์มาร์เกตในเขตจังหวัดพิษณุโลก จานวน 103 ตัวอย่าง มาทาการแยกเชื้อ Escherichia coli ที่ลดความไวต่อยา cephalosporin รุ่น 3 โดยการนาตัวอย่างเนื้อสัตว์มาแยกเชื้อบนอาหารเลี้ยงเชื้อที่มีการเติมยา cefotaxime (เลือก 1 โคโลนีต่อ 1 ตัวอย่าง) ในการศึกษานี้พบเชื้อ E. coli ในตัวอย่างเนื้อสัตว์จานวน 65 ตัวอย่าง (ร้อยละ 63) การทดสอบความไวต่อยาปฏิชีวนะพบว่าเชื้อส่วนใหญ่มีการดื้อยาหลายขนาน และพบเชื้อจานวน 18 ไอโซเลท (ร้อยละ 28) ลดความไวต่อยาที่มีประสิทธิภาพสูง คือ imipenem นอกจากนี้ยังพบเชื้อที่มีการสร้างเอนไซม์ Extended Spectrum Beta-Lactamase (ESBL) ถึงร้อยละ 69 การตรวจหายีนที่ควบคุมการสร้าง ESBL 2 ชนิด คือ blaTEM และ blaSHV โดยวิธี Polymerase Chain Reaction (PCR) พบ ยีน blaTEM และ blaSHV ในเชื้อจานวน 27 และ 1 ไอโซเลท ตามลาดับ ซึ่งเป็นเชื้อที่แยกได้จากเนื้อไก่ทั้งหมด ผลการศึกษาในครั้งนี้แสดงให้เห็นว่ามีการปนเปื้อนของเชื้อ E. coli ดื้อยาหลายขนานรวมทั้งเชื้อที่มีการสร้างเอนไซม์ ESBLในเนื้อสัตว์ปีก ซึ่งอาจถ่ายทอดสู่คนได้โดยการบริโภคและส่งผลถึงสุขภาพของประชาชนต่อไป คำสำคัญ: เอสเชอริเชียโคไล การดื้อยาปฏิชีวนะหลายขนาน อีเอสบีแอล สัตว์ปีก         The potential role of poultry meat products as a possible reservoir for resistant bacteria was assessed. In this study, 103 poultry meat samples (chicken and duck) obtained from supermarkets in Phitsanulok province were investigated for the presence of antimicrobial resistant Escherichia coli. Samples were inoculated onto cefotaxime-containing media for isolation of E. coli with reduced susceptibility to broad spectrum cephalosporin (one isolate/sample). E. coli isolates were detected in 65 (63%) of the poultry meat samples. Antimicrobial susceptibility testing showed that the majority of isolates were classified as multidrug resistant E. coli. Reduced susceptibility to imipenem, the high efficacy antibiotic, was found in 18 isolates (28%). Interestingly, a high rate of Extended Spectrum Beta-Lactamase (ESBL)-producing E. coli (69%) was detected. The presence of ESBL-encoding genes (blaTEM and blaSHV) was investigated by Polymerase Chain Reaction (PCR). blaTEM and blaSHV genes were found 27 and 1 E. coli isolates, respectively, all from chicken meat. These results pose a serious health concern as contamination of poultry meat products by Multidrug resistant E. coli (MDR E. coli), especially the ESBL-producing isolate, may contribute to the transmission of resistant bacteria from food to humans. Keywords: Escherichia coli, multidrug resistance, ESBL
Keywords: เอสเชอริเชียโคไล การดื้อยาปฏิชีวนะหลายขนาน อีเอสบีแอล สัตว์ปีก Escherichia coli, multidrug resistance, ESBL